Implementasi Design Thinking Dalam Meningkatkan User Experience Pada Website Bemitory Milik Bem Fasilkom Unsika - Irna Purnahasanah; Garno, Garno; Betha Nurina Sari (Innovative: Journal Of Social Science Research, 2025)
The development of information technology demands improved user experience (UX) in web-based applications. This study aims to recommend a redesigned user interface (UI) for the Bemitory website owned by BEM Fasilkom Unsika and evaluate its usability based on three ISO 9241-11 aspects: effectiveness, efficiency, and satisfaction. The research method used is Design Thinking, consisting of five stages: empathize, define, ideate, prototype, and testing. This approach explores the needs and expectations of users, particularly students of Fasilkom. The results show an increase in the average System Usability Scale (SUS) score from 45 to 94,5 after redesign. This score is categorized as “Best Imaginable” in adjective rating, grade “A”, and “Acceptable” in acceptability. Task completion effectiveness reached 100%, and time-based efficiency reached 0.16 goals per second. These findings indicate that implementing Design Thinking in website development effectively improves user satisfaction, efficiency, and effectiveness, and is suitable for creating more user-centered UI designs. Keywords: Design Thinking, System Usability Scale, UI, UX, Website